2004
DOI: 10.1001/archneur.61.1.35
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinsonian Phenotype of Spinocerebellar Ataxia Type 2

Abstract: We conclude that SCA2 is a minor cause of familial parkinsonism, particularly in Taiwan. The parkinsonian phenotype is associated predominantly with a shorter abnormal range of CAG repeat lengths and older onset age. Because of the clinical resemblance among familial parkinsonisms, we suggest that SCA2 should be excluded in cases of familial parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
63
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 19 publications
(20 reference statements)
4
63
0
Order By: Relevance
“…23,24 The results of Sobczak et al 25 showed that the CAA interruptions are major determinants of the CAG repeat folding in the SCA2 transcripts. The SCA2 transcripts interrupted by the CAA should generate shorter branched hairpins and the uninterrupted repeats transcripts form single slippery hairpins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 The results of Sobczak et al 25 showed that the CAA interruptions are major determinants of the CAG repeat folding in the SCA2 transcripts. The SCA2 transcripts interrupted by the CAA should generate shorter branched hairpins and the uninterrupted repeats transcripts form single slippery hairpins.…”
Section: Discussionmentioning
confidence: 99%
“…The patients who carried SCA2 expansions with and without interruptions show two different phenotypes. 23,24 It may be caused by the different CAG repeat folding that would interact differently with doublestranded RNA binding proteins and interfere with mRNA transcription or translation. 24 That structural organization of CAG expansions with interruption associate with phenotypic variation has been also reported in other neurodegenerative disorders such as SCA1 (see ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical and pathologic findings emphasize the need to evaluate the significance of polyglutamine repeat expansions of these genes in PD worldwide. [4][5][6][7][8][9] Most studies performed to date, including this study, are biased by case selection at specialist movement disorders clinics. However, to get a better estimate of the frequency of repeat expansions in such a setting, their relative contribution to disease worldwide, we performed a large multicenter study with members of the Genetic Epidemiology of Parkinson's Disease (GEO-PD) Consortium.…”
mentioning
confidence: 99%
“…Likewise, a study in Asian patients identified 7 SCA2 carriers that showed overlapping phenotype with ataxia such as dysarthria and postural instability. 7 However, such patients would not have been included in this study because the inclusion criterion was diagnosis of PD. Our study also did not investigate the role of interruptions in the repeats on PD, thus we cannot draw any conclusions for this subcategory of patients.…”
mentioning
confidence: 99%